4A Plan for Instruction: Elaborating the Psychosocial Dimensions - Lekshmi G S, Durga (International Journal of Psychosocial Rehabilitation, 2020)
21st century teaching learning society witnesses a plethora of new teaching strategies, designs, and new instructional plans. Among the developed ones, a majority of the instructional models and plans are befitting to certain select disciplines only. It is the need of the hour to incorporate all the essential principles of learning under a single plan of instruction. The author, being a teacher educator since a decade, felt the need of a new instructional plan which would be able to facilitate the teacher- learner needs of various disciplines propose a new plan of instruction under the title ‘4A Plan for Instruction’. The instructional plan is the output of the author’s doctoral research. The present paper elaborates the psychosocial theories that are utilized for the development of the instructional plan. The instructional plan is sequenced in four instructional phases namely Acceleration, Acquisition, Affirmation and Amplification. The present instructional plan can be utilized for instructing multi discipline and various grade levels.